Diseño y aplicación de una Guía de Práctica Clínica para el manejo de farmacointeracciones desde la oficina farmacéutica - Laiza Vidal, Jhanett Sandra (2020)
ABSTRACT The Pharmacist of the pharmaceutical office has an important role in patient orientation regarding the proper use of their medications, being necessary to provide tools that support their training. To meet this need, the present study was proposed whose objective was to design and apply a clinical practice guide for the management of drug interactions from the pharmaceutical office. The study was developed in three phases; First phase: information was collected on the knowledge of twenty Pharmacists from the pharmaceutical office about drug interactions through a test and a survey and from this criteria were taken to design the guide; second phase: the guide was designed based on reliable scientific evidence, which was evaluated by experts; third phase: this guide was applied in a pharmaceutical office after training the Pharmacist and the identified potential drug interactions were reported after applying the information in that guide. In the First phase the level of knowledge of the Pharmacist about drug interactions was excellent (0%), good (40%), regular (55%) and low (5%), which showed the need for the present investigation, in addition no record of drug interactions was found in the pharmaceutical offices; second phase: the designed guide consisted of general information on drug interactions and a detailed procedure for their identification; third phase: after its application, 55 potential drug interactions classified as serious in 7,27%, moderate 74,55% and mild 18,18% were identified. Therefore, with a tool that allows the Pharmacist to train on issues of importance regarding the pharmacotherapy of the patient, care and guidance in the pharmacy office can be improved.